KINERJA PELAKSANA PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERDESAAN DI DESA NUSAPATI KECAMATAN SUNGAI PINYUH KABUPATEN PONTIANAK - Wawan Kurniawan E.42009008 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2022)
Writing articles to provide insight into the performance of implementing the National Program for Community Empowerment ( PNPM) Rural Village Nusapati Pinyuh River District. Issues regarding the performance of PNPM-MP is happening is quite interesting to study, given the policy of PNPM Rural program still can not be fully understood by the public in the implementation. It is difficult for people to accept, understand it and implementing the programs. So often goes wrong in exercising their understanding and interpretation of programs in the field. In addition, people still think that the PNPM Rural is budget support to the community. Then executor or actors involved in program implementation is still difficult PNPM Rural, because the quality of work, quantity of work and toughness offender program is still lacking and weak control program activity by actors at the village leve. So as to grow and develop with the advanced role, self-help, community participation and empowerment will be obstacles and difficult people to do. Through writing this essay is also intended, so that the performance- PNPM Mandiri in Rural Villages Nusapati good views of the quality of work, quantity of work and toughness can be realized in accordance with the expectations of society.Keywords : Performance , Implementation of PNPM Rural.